Preparation and properties of low protein latex - Sunny Sebastian M; Thomas E V; Valsa George (Papers presented at the IRMRA 18th Rubber Conference, Mumbai, January 20-21, 2000. p105-109)
Residual proteins present in natural rubber (NR) latex products can cause allergic reactions in sensitized people. Chlorination and leaching are the methods commonly employed for reducing extractable proteins (EP) in latex products. Chlorination can adversely affect the physical properties of latex films. Well leached films on storage again show the presence of EP. This is due to the migration of EP to the surface from interior layer. Hence reduction of EP in latex itself can solve allergic reactions to latex proteins to a great extent. This paper reports the preparation and properties of a latex low in EP. In conventionally sulphur vulcanized films of this low protein latex (LPL), EP content is very low. Physical properties of vulcanized LPL films are good, eventhough slightly less than that of films prepared from standard centrifuged latex (SCL).
Keywords: Low protein latex